Trade union view: Labour strikes in a transition society - Martinic, Marija (Sociološki pregled, 2020)
The review analyzes the strategies of trade unions in the transition society of Serbia. The article defends the hypothesis of social dialogue as an optimal democratic mechanism. The results of various political strategies of trade unions lead to the conclusion that the model of contractual cooperation is the only one in which it is possible to preserve the independence of trade unions.